Inspiration, Perspiration, and Time Operations and Achievement in Edison Schools - Gill, Brian (RAND Corporation, 2005)
In 2000, Edison Schools, the nation's largest education management organization, asked RAND to analyze its achievement outcomes and design implementation. RAND evaluated Edison's strategies for promoting student achievement in its schools, how it implemented those strategies, how its management affected student achievement, and what factors explained differences in achievement trends among its schools.